2020
DOI: 10.1093/jac/dkz542
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of NDM-1-producing Morganella morganii and Proteus mirabilis in a single patient in Portugal: probable in vivo transfer by conjugation

Abstract: Objectives To decipher the genetics of acquisition of carbapenemase-encoding genes identified in two carbapenem-resistant Enterobacteriaceae recovered from a single patient in Portugal. Methods Carbapenemase genes were searched by PCR assays and mating-out assays were performed to further characterize the plasmid support of the carbapenemase genes. Genetic characterization of the plasmid supports was performed by whole-plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
0
23
1
Order By: Relevance
“…GES-5 and GES-6 have been found sporadically, with the exception of one hospital in Lisbon where K. pneumoniae isolates co-harboring bla KPC-3 and bla GES-5 represented 17% of the isolates [ 16 ]. Although NDM producers have been recently detected in a single patient in Lisbon [ 18 ], no bla NDM-1 was found in gulls in our study, suggesting its still low diffusion rate. While ST940 was the predominant E. coli background identified from gulls in our study, this ST had not been identified in Portugal before and, to the best of our knowledge, has been exclusively identified among NDM-5-producing E. coli isolates in the US [ 36 ].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…GES-5 and GES-6 have been found sporadically, with the exception of one hospital in Lisbon where K. pneumoniae isolates co-harboring bla KPC-3 and bla GES-5 represented 17% of the isolates [ 16 ]. Although NDM producers have been recently detected in a single patient in Lisbon [ 18 ], no bla NDM-1 was found in gulls in our study, suggesting its still low diffusion rate. While ST940 was the predominant E. coli background identified from gulls in our study, this ST had not been identified in Portugal before and, to the best of our knowledge, has been exclusively identified among NDM-5-producing E. coli isolates in the US [ 36 ].…”
Section: Discussioncontrasting
confidence: 84%
“…GES-5 was mainly found sporadically with the exception of one hospital in Lisbon, where it represented 17% of the carbapenemase-producing K. pneumoniae isolates [ 16 ]. Although NDM producers have been recently detected in a single patient in Lisbon [ 18 ], they are still infrequent in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid transfer studies. The transferability of the plasmid carrying the NDM-5encoding gene was evaluated for all NDM-5-producing E. coli by mating-out assays using the filter-mating method as described previously (23). NDM-5-positive E. coli isolates were used as donors and azide-resistant E. coli J53 strain as recipient.…”
Section: Methodsmentioning
confidence: 99%
“…Ongoing resistance genes or virulence factors acquisition via mobile genetic elements (MGEs) including integrative and conjugative elements (ICEs) and mobilizable genomic islands (MGIs) has promoted M. morganii to become a new clinical treatment challenge ( Flannery et al, 2009 ; Schultz et al, 2017 ). Resistance genes were mainly plasmid mediated and harbored by various transposons or integrons, such as bla KPC–2 -carrying IncP6 plasmid ( Kukla et al, 2018 ), bla OXA–181 -carrying IncN plasmid ( McGann et al, 2015 ), bla NDM–1 -carrying IncC plasmid ( Aires-de-Sousa et al, 2020 ), bla NDM–5 -carrying IncX3 plasmid ( Guo et al, 2019 ), bla IMP–27 -carrying Tn 7 transposon ( Walkty et al, 2018 ), bla CTX–M–3 -carrying Tn 6741 transposon ( Luo et al, 2020 ), cfr -carrying Tn 7 transposon ( Chen et al, 2019 ) and bla GES–5 -carrying In 1390 integron ( Moura et al, 2018 ), which have significantly contributed to the increased levels of resistance in M. morganii .…”
Section: Introductionmentioning
confidence: 99%